India : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This report describes recent economic developments in India. It highlights that the real GDP growth accelerated from 6u percent in 1994/95 to 7 percent in 1995/96, reflecting mainly the growing response in the industrial sector to the earlier reforms. Industrial production rose 12 percent during 1995/96, led by a robust expansion in manufacturing output. The strong performance in the manufacturing sector was more broadly based than in previous years, with particularly rapid growth in capital goods and consumer durables. Growth in both mining output and electricity generation also remained buoyant.